2011
DOI: 10.1007/s10641-011-9942-8
|View full text |Cite
|
Sign up to set email alerts
|

Movements of lumpsucker females in a northern Norwegian fjord during the spawning season

Abstract: The lumpsucker Cyclopterus lumpus is distributed throughout the North Atlantic Ocean and migrates considerable distances between offshore feeding areas and shallow inshore spawning grounds. The number of the lumpsucker has declined since the mid 1980s, probably as a result of overexploitation. The lumpsucker is the preferred host of the sea louse Caligus elongates, which is a problem for marine aquaculture. However, little is known about the biology of the lumpsucker. The aims of the study were to 1) examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…They are often found mid-water as a frequent by-catch at 0-80 meters and occasionally feeding over abyssal waters up to 380 meters (Able & Irion 1985). Mitamura et al (2012) observed females migrating between neighboring fjords in search of spawning males, before residing for approximately 1-3 weeks to spawn. Lumpfish are active swimmers, often observed swimming against the current when performing migratory movements away from shore (Mitamura et al 2012), but can also exploit water currents facilitate rapid migrations to feeding grounds for lumpfish (Rusyaev 2013).…”
Section: Feeding Habitat Preferences and Migrations Of Adult Lumpfishmentioning
confidence: 99%
See 4 more Smart Citations
“…They are often found mid-water as a frequent by-catch at 0-80 meters and occasionally feeding over abyssal waters up to 380 meters (Able & Irion 1985). Mitamura et al (2012) observed females migrating between neighboring fjords in search of spawning males, before residing for approximately 1-3 weeks to spawn. Lumpfish are active swimmers, often observed swimming against the current when performing migratory movements away from shore (Mitamura et al 2012), but can also exploit water currents facilitate rapid migrations to feeding grounds for lumpfish (Rusyaev 2013).…”
Section: Feeding Habitat Preferences and Migrations Of Adult Lumpfishmentioning
confidence: 99%
“…The migratory behavior of lumpfish is similar to that of coastal benthic teleosts, but adults are also frequently found mid-water in open oceans outside the spawning season (Cox & Anderson 1922;Andrijasev 1964;Myrseth 1971;Davenport & Kjorsvik 1986). As a semi-pelagic species, it spends most of its life at offshore feeding grounds at deep water before conducting an active migration over great distances towards shallow coastal waters to spawn between winter and early spring (Myrseth 1971;Blacker 1983;Davenport 1985;Goulet et al 1986;Holst 1993;Mitamura et al 2012). …”
Section: The Lumpfishmentioning
confidence: 99%
See 3 more Smart Citations